Chronic hepatitis C virus infection is associated with all‐cause and liver‐related mortality in a cohort of HIV‐infected patients with alcohol problems. (24th October 2013) - Fuster, Daniel; Cheng, Debbie M.; Quinn, Emily K.; Nunes, David; Saitz, Richard; Samet, Jeffrey H.; Tsui, Judith I.
Abstract Aims To assess the association between hepatitis C virus (HCV) infection and overall and liver‐related death in human immunodeficiency virus (HIV)‐infected patients with alcohol problems. Design We analyzed data from a cohort of HIV‐infected adults with current or past alcohol problems enrolled between 2001 and 2003, searching for causes of death until 2010 using the National Death Index. Setting and participants Participants were HIV‐infected adults with current or past alcohol problems, recruited in Boston, MA from HIV clinics at two hospitals, homeless shelters, drug treatment programs, subject referrals, flyers and another cohort study with comparable recruitment sites. Measurements The primary and secondary outcomes were all‐cause and liver‐related mortality, respectively. The main independent variable was hepatitis C virus (HCV) RNA status (positive versus negative). Mortality rates and Kaplan–Meier survival curves were calculated by HCV status for both overall and liver‐related mortality. Cox proportional hazards models were used to assess the association between HCV infection and overall and liver‐related death, adjusting for alcohol and drug use over time. Findings A total of 397 adults (50% HCV‐infected) were included. As of 31 December 2009, 83 cohort participants had died (60 HCV‐infected, 23 HCV‐uninfected; log‐rank test P < 0.001), and 26 of those deaths were liver‐related (21 HCV‐infected, five HCV‐uninfected; log‐rank test P < 0.001). All‐cause and liver‐related mortality rates were 4.68 and 1.64 deaths per 100 person‐years for HCV‐infected patients and 1.65 and 0.36 per 100 person‐years for those without HCV, respectively. In the fully adjusted Cox model, HCV infection was associated with both overall [hazard ratio (HR) = 2.55, 95% confidence interval (CI) = 1.50–4.33, P < 0.01], and liver‐related mortality (HR = 3.24, 95% CI = 1.18–8.94, P = 0.02]. Conclusion Hepatitis C virus infection is associated independently with all‐cause and liver‐related mortality in human immunodeficiency virus‐infected patients with alcohol problems, even when accounting for alcohol and other drug use.